Primary Signet Ring Cell Carcinoma of the Lung with Cerebellar Metastasis Showing Full Response to Cisplatin and Docetaxel Therapy. (26th December 2013) - Kocas, Onur; Selcukbiricik, Fatih; Bilici, Ahmet; Kanıtez, Metin; Yildiz, Serdar; Avci, Suna; Tanik, Canan
Abstract : Introduction . Primary signet ring cell carcinoma (SRCC) of the lung is a very rare disease. We describe a new case of primary SRCC of the lung with cerebellar metastasis, which responded well to the therapeutic approach with cisplatin and docetaxel. Case Report . A 41-year-old female patient (nonsmoker) was consulted to our oncology outpatient clinic after cerebellar metastasectomy. The histopathological diagnosis was SRCC metastasis. The primary tumor was unknown. The PET-CT imaging showed a hypermetabolic mass in the right middle lobe of the lung and hypermetabolic mediastinal lymph node stations. Oesophagogastroduodenoscopy and colonoscopy showed no evidence of gastrointestinal system tumor. The clinical diagnosis of primary SRCC of the lung was made and the administration of six rounds of cisplatin and docetaxel treatment was planned. After the chemotherapy the PET-CT scan to evaluate the therapy response showed full metabolic regression of the primary tumor and the mediastinal lymph nodes. There was no evidence of new metastasis. Conclusion . Primary SRCC of the lung is a very rare disease with poor prognosis. There are not many cases in literature and no standardized chemotherapy protocols. Cisplatin and docetaxel may be a good treatment option.